The Effect of Alginate-Chitosan/Quaternary Chitosan Concentration on The Release of Propolis (Tetragonula Spp.) in Hydrogel Wound Dressings - Iqbal Nugroho; Priskilla Meliana Hutahaean; Melania Diu; Aulya Indah Purwanty; Annisa Aulia Savitri (Journal of Science and Technology Research for Pharmacy, 2025)
The increasing incidence of acute and chronic wounds globally requires the development of effective wound dressings. This study aims to formulate and analyze the release profile of propolis extract (Tetragonula spp.), which has potential biological activity for wound healing, from a hydrogel wound dressing (HWD) based on alginate-chitosan/quaternary chitosan biocomposite as a delivery system that can control its release. Propolis extract, which has been tested positive for alkaloids, flavonoids, tannins, and steroids/triterpenoids, was formulated into four HWD formulas (F1-F4) with varying ratios using the solvent casting method. The results of the release test in PBS medium at pH 7.4 at 37 C for 48 hours showed that all formulas produced a gradual release. The results of the One-Way ANOVA test on the final cumulative release showed no statistically significant differences (p>0.05). However, descriptively, Formula F2 (4% alginate-8% quaternary chitosan) showed the highest release percentage (99.85%) with the most stable rate, followed by F4 (98.71%), while F3 with high chitosan showed the lowest percentage (86.65%). The best release kinetics analysis followed the Higuchi model (R² ≥ 0.95), indicating that the release mechanism was controlled by diffusion. It was concluded that variations in the alginate and chitosan/quaternary chitosan ratios affected the release pattern and rate, and Formula F2 with a balanced ratio produced an optimal controlled release profile, making it the most ideal candidate for further development as a therapeutic hydrogel wound dressing.